A game theory-based design of incentive schemes for social cloud services. (2018) - Kuada, Eric
This paper presents the design of incentive schemes that encourage the contribution of resources to the opportunistic cloud services (OCS) social cloud platform as well as the efficient usage of such resources. A game theoretic approach has been employed to model and design the incentive schemes with two game models presented. The existence of a pure strategy Nash equilibrium for both the cooperative and non-cooperative games has been proven. Three base incentive schemes have also been presented. These schemes are the dominant strategy scheme, equi-profit scheme, and dominant equi-profit scheme. Evaluation of the incentive schemes are performed and conclusion made that the schemes meet the desired properties of budget-balance, ex-post individual rationality, incentive compatibility, allocative efficiency, robustness, and flexibility to accommodate changing user behaviour on the OCS social cloud services platform.